Recent Advances in Various Inorganic Nanoparticle Embedded Chitosan-based Multifunctional Materials for Wound Healing - Bhattacharya, Dipsikha; Ray, Lipika; Pramanik, Panchanan; Pandey, Jitendra K. (Current Nanomedicine, 2023)
Scarless wound management remains a clinical challenge worldwide because of its complicated and overlapping phases of inflammation, clearing, and regeneration. Among the currently available dressing materials, hydrogels have attracted emerging attention as potential wound dressing materials because of their specific properties, such as porosity, tissue-mimicking architecture, softness, and improved mechanical, biological as well as physicochemical properties. However, naturally driven hydrogels have shown several advantages over conventional hydrogels because of their biodegradability, biocompatibility, high mechanical strength, and functionality. Recently, nanoparticle (NPs) integrated polymeric hydrogels (metals, non-metals, metal oxides, and polymeric moieties) have been established as analogous to these naturally driven hydrogels because of the synergistic effects of the NPs and polymers in the three-dimensional composite material. Over the years, researchers have reported the synthesis and potential applications of diverse inorganic and organic nanocomposite gels with antioxidant or antibacterial properties where they have exploited the intelligent incorporation of biomolecules into the NP-polymeric network that are beneficial for wound healing. Among various natural polymers as hydrogel matrix, chitosan-mediated hydrogel dressings have received extensive interest resulting in improved mechanical, biological, and physicochemical properties due to the well-reported antibacterial, antitumor, antioxidant, and tissue regeneration efficacies of chitosan polymer. This review is intended to summarize the recent developments of inorganic nanoparticle-incorporated chitosan-based hydrogels as wound dressing materials where various synthetic methodologies of these nanocomposite gels are extensively discussed via incorporating nanoparticles, active biomolecules, and other substances into the intrinsic structure of the gels. In addition, the future and prospects of chitosan-based nanocomposite hydrogels as a novel wound dressing as well as tissue engineering materials are also highlighted.
Keywords: multifunctional